1997
DOI: 10.1093/qjmed/90.12.781
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure: factors influencing nephrology referral and outcome

Abstract: We investigated the incidence, factors affecting referral and outcome of acute renal failure (ARF), in an unselected (predominantly Caucasian) population in the Grampian region of Scotland served by a single renal unit. Case-notes were examined for all patients with a serum creatinine > or = 300 mumol/l. ARF (311 patients) was defined as a temporary rise in serum creatinine > or = 300 mumol/l, or, if the patient died during the acute illness, clinical features indicating acute deterioration of previously norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
113
5
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(128 citation statements)
references
References 9 publications
6
113
5
4
Order By: Relevance
“…One element that has been examined is which physicians care for patients with AKI following hospital discharge. Studies indicate that most survivors of AKI are not cared for by nephrologists [89][90][91][92] . Although data derived largely from observational cohort studies suggest that referral to nephrology care is associated with improved survival 93 , causality remains to be proven and the elements of care that drive this potential benefit have not been identified.…”
Section: Follow-up Carementioning
confidence: 99%
“…One element that has been examined is which physicians care for patients with AKI following hospital discharge. Studies indicate that most survivors of AKI are not cared for by nephrologists [89][90][91][92] . Although data derived largely from observational cohort studies suggest that referral to nephrology care is associated with improved survival 93 , causality remains to be proven and the elements of care that drive this potential benefit have not been identified.…”
Section: Follow-up Carementioning
confidence: 99%
“…Data from multiple international studies have shown that delayed referral to a nephrologist is a significant problem and is associated with a higher prevalence of uremic complications at the initiation of dialysis, with increased hospitalization and higher cost of care. [21][22][23][24] In addition, Arora and colleagues demonstrated that incident dialysis patients who were referred late (defined as the first encounter with a nephrologist occurring within 4 months of dialysis initiation) were significantly more likely to have hypoalbuminemia and hypocalcemia and less likely to have received EPO and a permanent vascular access before the first hemodialysis. Late referrals to a nephrologist were also associated with lower levels of renal function at dialysis initiation, as documented by higher serum creatinine and a higher proportion of patients with predicted glomerular filtration rate <5 mL/min per 1.73 m 2 .…”
Section: O R I G I N a L R E S E A R C Hmentioning
confidence: 99%
“…AKI is managed by a variety of specialities, renal wards, high-dependency wards, and intensive care units (ICU). A number of studies included ICU-treated patients (1)(2)(3)(4); others included only those with severe AKI (5,6) or included only those who required RRT (6 -8). Because AKI occurs more frequently in older people, the incidence of this condition is rising in accordance with demographic trends.…”
mentioning
confidence: 99%